Incidence of Malignancy in Nose and Paranasal Sinuses - Salman Aftab Ahmed, Sajid Rashid Nagra, Ghulam Dastgir Khan, Saleha Rashid, Zarmina Gul, Saad Rashid, (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To analyze the occurrence of malignancy in nose and paranasal sinuses and to identify the common type of nose and paranasal sinuses tumor. Study Type: Analytical study Place and Duration of Study: ENT Outpatients Department, Rai Medical College Teaching Hospital, Sargodha from 1st April 2017 to 31st March 2021. Methodology: Fifteen patients with nasal endoscopy performed for the diagnosis of tumors were enrolled. Lesion site and extent were determined through computed tomography imaging. Biopsy of each patient was performed under local anesthesia and histopathological findings were documented. Results: The mean age of patients was 55.3±3.3 years. Tumors of nose and paranasal sinuses were more common in the males (66%) than in the females (34%). It is revealed that majority of cases were diagnosed with squamous cell carcinoma 12 (80%) cases, 2 (13.3%) cases were diagnosed as adenocarcinoma and 1 (6.7%) case was diagnosed as adenoid cystic carcinoma. Conclusion: Squamous cell carcinoma was the main histopathological category of nose and paranasal sinuses tumor. Keywords: Sinonasal malignancies, Paranasal malignancies, Squamous cell carcinoma, Nose, Wood dust